North Korean children: nutrition and growth - Soo-Kyung Lee (Korean Society of Pediatric Endocrinology, 2017)
North Korea suffered from severe famine in the mid-1990s; this impacted many areas, including people's transnational movement, child growth, and mortality. This review carefully examined nutritional status trends of children in North Korea using published reports from national nutrition assessment surveys. Nutritional adaptation of North Korean child refugees living in South Korea was also studied with their growth and food consumption, using published researches. The nutritional status of children in North Korea has recovered to a "low" level acute malnutrition status and a "medium" level chronic malnutrition status. Large disparities by geographic region still remain. North Korean child refugees in South Korea were significantly shorter and lighter than their age- and sex-matched South Korean counterparts (P<0.05); however, North Korean child refugees were catching up, and weight was improving faster than height. Linear growth retarded (height for age Z-score < -1) North Korean children showed a significantly higher respiratory quotient than nonlinear growth retarded children, indicating metabolic adaptation responding to the food shortage. These changes, accompanied by abundant access to food in South Korea, have led to the elimination of significant differences in the obesity ratio between North Korean and South Korean children living in South Korea after approximately 2 years of residency. This nutritional adaptation may not be beneficial to North Korean child refugees, especially given the prediction of Barker's theory. The lack of studies prevented a better understanding of this issue; therefore, large cohort studies, preferably with random sampling strategies, are needed to further understand this issue and to design appropriate interventions.